Observing treatment outcomes in other patients can elicit augmented placebo effects on pain treatment: a double-blinded randomized clinical trial with patients with chronic low back pain. Issue 7 (17th July 2022) - Schwartz, Marie; Fischer, Laura-Marie; Bläute, Corinna; Stork, Jan; Colloca, Luana; Zöllner, Christian; Klinger, Regine
Abstract : Supplemental Digital Content is Available in the Text. Social observational learning can augment the effect of pain medication in patients with chronic low back pain leading to a reduction in perceived pain-related disability. Abstract: Clinical research on social observational learning (SoL) as an underlying mechanism for inducing expectancy and eliciting analgesic placebo effects is lacking. This double-blinded randomized controlled clinical trial investigated the influence of SoL on medication-augmenting placebo effects in 44 patients with chronic low back pain. Our hypothesis was that observing positive drug effects on pain and mobility in another patient could increase pain reduction and functional capacity. To test this, we compared the effects of observing positive treatment outcomes in a sham patient (the social learning group [SoLG]) vs hearing the same sham patient report neutral effects (the control group). In the SoLG, the sham patient told peers about pain reduction due to amitriptyline and demonstrated his improved mobility by bending forwards and sideways while he told the control group only that he was taking amitriptyline. The primary outcome was a reduction in clinical low back pain self-ratings. The secondary outcome was perceptions of pain-related disability. The exploratory outcome was mood and coping statements. Data collection occurred before and after the intervention and 2 weeks later. After the intervention, pain decreased in both groups (F [1, 41] = 7.16, P < 0.05, d = 0.83), with no difference between groups. However, the SoLG showed a significantly larger decrease in perceived disability (F [1, 41] = 5, P < 0.05, d = 0.63). The direct observation of patient with chronic low back pain of positive treatment outcomes in the sham patient seems to have enhanced the treatment effects while indirect verbal reports of reduced pain did not.